2021
DOI: 10.3103/s1052618821060066
|View full text |Cite
|
Sign up to set email alerts
|

Application of Dimensional Analysis for Calculating the Total Misalignment between a Seal and a Shaft

Abstract: For shaft-seal connections, the dependence is determined and an algorithm for calculating the total deviation from alignment and the total radial runout in the shaft-seal connection is tested. It is recommended that the designers of a manufactured gearbox increase the requirements on the dimensions of the parts forming the dimensional chain that determines the total deviation from alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…And if, until recently, IT technologies were used mainly in the field of personnel and financial management, now digital technologies are used in the design, production and maintenance of products to optimize processes, reduce costs and produce defective products (Erohin et al, 2019a). But the introduction of digital technologies requires a certain level of knowledge from technologists, which is not enough in the labor market (Erohin et al, 2019b). Therefore, it is necessary to introduce the most automated technologies for conducting business processes.…”
Section: Resultsmentioning
confidence: 99%
“…And if, until recently, IT technologies were used mainly in the field of personnel and financial management, now digital technologies are used in the design, production and maintenance of products to optimize processes, reduce costs and produce defective products (Erohin et al, 2019a). But the introduction of digital technologies requires a certain level of knowledge from technologists, which is not enough in the labor market (Erohin et al, 2019b). Therefore, it is necessary to introduce the most automated technologies for conducting business processes.…”
Section: Resultsmentioning
confidence: 99%
“…Methods and means of research. When determining the arithmetic mean, standard deviation, and a number of other characteristics, methods of mathematical statistics and probability theory had used [1]. In order to determine the measurement error and its components, standard metrological evaluation methods had used.…”
Section: Methods and Means Of Researchmentioning
confidence: 99%
“…And the measuring instruments used here are, most often, universal measuring instruments for linear dimensions. But even when repairing machines, it is necessary to control the complex geometric dimensions of body parts, their deviations in the shape and location of surfaces [1,2], and also to select parts in sets by weight [3].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of existing methods for calculating losses due to measurement error showed that all of them are purely theoretical and do not take into account the specifics of a particular technological process (Wu, 2013). A feature of modern engineering production is the appointment of such tolerances that allow for a certain margin of accuracy in the joints (Leonov & Shkaruba, 2019;Leonov et al, 2020c), as well as the necessary accuracy of dimensional chains (Erokhin et al, 2021), but at the same time there is a decrease in tolerances, an increase in the accuracy of processing and, as a result, the need to use more accurate measuring instruments.…”
Section: Problem Statementmentioning
confidence: 99%